2018
DOI: 10.1515/opag-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Genotype X Environment Interaction for Yield of Pickling Cucumber in 24 U.S. Environments

Abstract: Reliable yield performance is important in cucumber because seed companies prefer to market cultivars adapted to multiple rather than single regions of the U.S. Also, growers benefit by using a cultivar that performs well in many environments. Future performance of cultivars is also important. The objectives of the study were to (i) evaluate the yield of cucumber genotypes over successive years and in different locations, and (ii) identify cucumber genotypes with high stability for yield. A diverse set of 22 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…These results indicated that the most traits exhibited high and significant differences, It also, suggesting that these traits were affected by changing environmental from year to year and sowing date to another sowing date. These results were in agreement with those found by Saglam and Yazgan, (1999), Mrinalini andDevi, (2017), andDia et al, (2018).…”
Section: Analysis Of Variancesupporting
confidence: 93%
“…These results indicated that the most traits exhibited high and significant differences, It also, suggesting that these traits were affected by changing environmental from year to year and sowing date to another sowing date. These results were in agreement with those found by Saglam and Yazgan, (1999), Mrinalini andDevi, (2017), andDia et al, (2018).…”
Section: Analysis Of Variancesupporting
confidence: 93%
“…The G · E interactions ranged from 8% to 21% among the yield traits. The magnitude of G · E variance (as compared with G) indicated that multienvironment cultivar evaluations are critical in muskmelon breeding programs (Dia et al, 2018). Furthermore, genotype (G) by year (Y) interactions were also highly significant for yield traits, suggesting that G · Y interactions are important to consider for developing stable cultivars adapted for a specific environment (Joshi et al, 2011).…”
Section: Fruit Yield and Its Componentsmentioning
confidence: 99%
“…Furthermore, genotype (G) by year (Y) interactions were also highly significant for yield traits, suggesting that G · Y interactions are important to consider for developing stable cultivars adapted for a specific environment (Joshi et al, 2011). The genotype (G) by location (L) interactions were also significant for these traits, indicating the need of regionalization of melon breeding programs (Dia et al, 2016a(Dia et al, , 2018. In a planting density study at two locations, Kultur et al (2001) found that G · L interactions had significant effects on FN, FW, and TFY in melons.…”
Section: Fruit Yield and Its Componentsmentioning
confidence: 99%
“…When a significant G × E is identified, subsequent stability analysis is often carried out to identify stable genotypes which exhibit consistently higher yield over several environments 4 . The presence of significant G × E has been found in growth and yield traits of several field 5 8 and vegetable crops 3 , 9 11 . In tomato ( Solanum lycopersicum L.), an economically important vegetable widely grown and consumed in the world, yield and quality traits were found to demonstrate strong G × E 12 – 16 .…”
Section: Introductionmentioning
confidence: 99%